Robotic Surgery with Computer Vision: A Case Study on Da Vinci Systems - Chowdary, Mutyala Dhatri; Koppireddy, Chandra Sekhar (Journal of Soft Computing Paradigm, 2025)
Robotic surgery is nowadays one of the most important changes in modern medicine, as it is more precise, less invasive, and has a shorter recovery time. This review addresses the integration of computer vision into robotic-assisted surgery, with a case study of the Da Vinci Surgical System. The equipment consists of robotic arms controlled by a surgeon’s console, which provides high-definition 3D imagery and superior motion control. Computer vision improves depth perception, real-time instrument tracking, and surgical image processing to guide instruments more precisely, helping to identify complex anatomical structures. This is a review-based study that uses over 50 peer-reviewed articles, manufacturer technical specifications, and published clinical performance data. No original experimental or observational patient data that was gathered. Simulation settings of synthetic tissue models, validated kinematics and multi-specialty clinical case reports are mentioned in the referenced works. The existing drawbacks are associated with cost, low automation, and human-based operation. Artificial intelligence, machine learning, and autonomous functions are likely to be developed further, and current feasibility is limited to AI-assisted imaging, anatomical landmark detection and simple camera automation. Full autonomy in surgery is still in the research phase and is expected to be adopted in 8 to 10 years. Developments in imaging, system assessment, and clinical studies reveal that computer vision will continue to change robotic surgery in every corner of the globe.
Keywords: Surgical robotics; Image-guided surgery; 3D surgical imaging; Instrument tracking; Depth perception enhancement; Motion control in surgery; Computer vision; Medical image processing; Surgical automation